If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -21 = x + 73 Reorder the terms: -21 + 3x = x + 73 Reorder the terms: -21 + 3x = 73 + x Solving -21 + 3x = 73 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -21 + 3x + -1x = 73 + x + -1x Combine like terms: 3x + -1x = 2x -21 + 2x = 73 + x + -1x Combine like terms: x + -1x = 0 -21 + 2x = 73 + 0 -21 + 2x = 73 Add '21' to each side of the equation. -21 + 21 + 2x = 73 + 21 Combine like terms: -21 + 21 = 0 0 + 2x = 73 + 21 2x = 73 + 21 Combine like terms: 73 + 21 = 94 2x = 94 Divide each side by '2'. x = 47 Simplifying x = 47
| -x+44=21 | | 21-3g=20+2g | | 5a+4a-6b= | | (9-p)3= | | y=0.5x^3-2x+2.5 | | e^2+7e+10= | | 2c+19=65 | | p(-4)=-9+p | | 16(3x-.25)= | | 0.5x^3-2x+2.5=y | | (z+5)(z-8)=0 | | 0.5x^3-2x+2.5=0 | | -4=-(x-3)+6(x-2) | | 5(c-8-3)-3(2c+12)=-84 | | 2x+x+2=5x-10 | | .05x+.10(200-x)=.45x | | 0.09w=1.8 | | (a+4)(a+5)=0 | | -132=-39 | | -(c+10)+3(2c-6)= | | -132=39 | | -3v-v=16 | | -9b=-117 | | 35x+9=55 | | -n+2n=4 | | -8b=-117 | | -7x-3=4 | | 6n-7=2n+17 | | 11x-4x^2-344= | | 1/3(s-2)=s+4 | | (x+9)(x+9)=18 | | 344=11x-4x^2 |